2014
DOI: 10.1039/c3nr06219h
|View full text |Cite
|
Sign up to set email alerts
|

Simple, green and high-yield production of single- or few-layer graphene by hydrothermal exfoliation of graphite

Abstract: Graphene is widely used as promising electronic material and devices, owing to its exceptional electronic and optoelectronic properties. Up to now, defect-free graphene has been limited to the method for controllable, reproducible and scalable mass production. A simple, green, and nontoxic approach for large-scale preparation of high quality graphene is produced by exfoliation of graphite sheets collaborated with intercalant (FeCl2) under hydrothermal conditions, the absence of defects or oxides in graphene wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 36 publications
2
55
1
Order By: Relevance
“…Nevertheless, we can make a hypothesis to explain the discrepancy between our and literature data on graphene cytotoxicity. Our MLG samples are composed of several graphene sheets (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), while the majority of the works utilize single-layer or FLG (pristine or oxidized). Studies mainly focused on the graphene sheet lateral size, rather than the number of layers [38,39].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we can make a hypothesis to explain the discrepancy between our and literature data on graphene cytotoxicity. Our MLG samples are composed of several graphene sheets (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), while the majority of the works utilize single-layer or FLG (pristine or oxidized). Studies mainly focused on the graphene sheet lateral size, rather than the number of layers [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…In fact, graphene was firstly exploited in material sciences and recently it showed to be a good candidate for the development of graphene-based electronics, photonics, composite materials, energy generation, energy storage and sensors [5][6][7][8][9]. Among all graphene forms, FLGs are easily produced in high yeld [10][11][12][13]. Low-cost procedures have also been described for the fabrication of large area films of FLG for electronics and opto-electronic applications [14].…”
Section: Introductionmentioning
confidence: 99%
“…24 All of the above studies give sufficient reason to believe that inorganic salt-assisted hydrothermal exfoliation is an efficient method for the preparation of large quantities of high-quality graphene from graphite. However, the detailed role of salt ions in the intercalation process has not been clearly elucidated, which hinders the rational design of highly-efficient intercalators.…”
Section: -15mentioning
confidence: 99%
“…Researchers have revealed that the van der Waals force between the two water molecules is decreased with increasing temperature in a condition of high temperature and high pressure. This indicates the water molecules are force-free and have vigorous Brownian motion of molecules under sonication-assisted hydrothermal conditions [25][26][27][28]. Interestingly, H 2 O is a polar molecule of a V-shaped structure and the surface tensions of water are close to h-BN in hydrothermal conditions, suggesting that water molecules can be adsorbed on BNNSs, and separate the flakes.…”
Section: Resultsmentioning
confidence: 99%